PENGARUH BAHASA MEDIA SOSIAL TERHADAP KEMAMPUAN MENULIS AKADEMIK SISWA SMP - Aulia Mita; Annur Assifa Syahira; Nurlisa Nurlisa (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This study aims to analyze the influence of social media language use on junior high school students' academic writing skills. Social media has become part of students' daily lives and influences their language habits, especially in the use of informal language, abbreviations, and sentence structures that do not conform to Indonesian language rules. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, documentation, and questionnaires involving 30 junior high school students as research subjects. The results show that high intensity of social media use tends to have an impact on decreasing spelling accuracy, choice of diction, and sentence structure in students' academic writing. Although social media has positive potential in increasing students' creativity and courage in expressing ideas, its negative impacts are more dominant if not balanced with directed language learning. Therefore, this study also examines the implementation of the Student Teams Achievement Divisions (STAD) cooperative learning model as an effort to address these issues. The results of the STAD implementation model showed an improvement in students' academic writing skills and awareness of using good and correct Indonesian. Therefore, innovative and collaborative learning is crucial to minimize the negative impact of social media language on students' academic writing skills.